Komunikasi Interpersonal Perangkat Desa Dengan Masyarakat Tunagrahita Dalam Pembentukan Rumah Harapan - Janah, Defi Asiatul; Pramudita, Yusvi Nur; Alfarizi, Muhammad Salman; Wijayani, Qoniah Nur (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This term is often used to describe the condition of individuals who have limitations in terms of cognitive abilities, physical development and social adaptation abilities. Individuals with mental retardation may need special support in various aspects of daily life, such as education, work, and social interactions. Every country cannot be separated from the problem of mental retardation, Indonesia has a law regarding the empowerment of the mentally retarded in Law No. 4 of 1997 concerning people with disabilities, and also the national action plan for people with disabilities 2009-2014. The formation of Rumah Harapan is a form of empowerment for the mentally retarded, with the main aim of helping them achieve their best potential and improving their quality of life as well as helping them achieve progress and be independent according to their abilities. In empowering the formation of houses of hope, interpersonal communication carried out by village officials as organizers with the mentally retarded community cannot be separated. The aim of this research is to identify how interpersonal communication is carried out by village officials in an effort to empower mentally retarded communities to build houses of hope. The research was carried out using a constructivist paradigm, a qualitative case study approach, collecting data from observations, interviews and analysis of village archive documentation. The results of this research are the use of simple sign language in accordance with the identification of communication elements and then speed up understanding of the interpersonal communication process.